PERANCANGAN STRATEGI RISIKO RANTAI PASOK DENGAN MENGGUNAKAN METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) DAN HOUSE OF RISK (HOR) (STUDI KASUS : UKM MRP.PAYAKUMBUH) - amanda, suci; Lubis, Fitriani Surayya; Hartati, Misra; Nurainun, Tengku; Devani, Vera (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2024)
UKM Mrp.Payakumbuh is located in Payakumbuh, West Sumatra, UKM Mrp.Payakumbuh operates in the clothing industry. The problem of delays in raw materials from suppliers causes the process to take a long time. A long supply chain process can result in the company experiencing losses. There are still many rejected products, and identification of sources of risk from suppliers, raw materials, distributors and consumers is not optimal. The aim of this research is to determine chain risk priorities. supplies that must be handled and designing a supply chain risk strategy for SMEs Mrp. Payakumbuh. The results of this research obtained thirteen risks which were prioritized in this research, UKM Mrp. Payakumbuh uses the House of Risk (HOR) method to identify existing risks. In the HOR Phase 1 method, there are 20 risk events and 20 risk agents. In HOR Phase 2, this stage requires the output results in HOR Phase 1, namely designing an appropriate risk management strategy in accordance with the 8 priority risks. In HOR Phase 2 there are 13 proposed preventive actions with codes PA1 to PA13 and a priority risk management proposal is obtained, then code PA2 is obtained. Code PA2 is Controlling storage areas every month.